SDSS J002531.46-104022.2 at z = 0.30: A candidate for the (ultra)luminous infrared galaxy to optical quasar transition - Villar-Martín, M.; Emonts, B.; Rodríguez, M.; Pérez Torres, M.; Drouart, Guillaume (2013)
Using data obtained with the Australia Telescope Compact Array (ATCA), we have characterized the amount, spatial distribution and kinematics of the molecular gas in the merging, double-nucleus type 2 quasar (QSO) SDSS J002531.46-104022.2 (hereafter SDSS J0025-10) at z = 0.30 using the CO(1-0) transition. This is one of the scarce examples of quasar host galaxies where the CO emission has been resolved spatially at any redshift. We infer a molecular gas mass MH2= (6 ± 1) × 109M?, which is distributed in two main reservoirs separated by ~9 kpc. It has been found that ~60 per cent of the gas is in the central region, associated with the QSO nucleus and/or the intermediate region between the two nuclei. The other 40 per cent is associated with the northern tidal tail and is therefore unsettled. With its high infrared (IR) luminosity LIR = (1.1 ± 0.3) × 1012 L?, SDSS J0025-10 is an analogue of local luminous infrared galaxies (LIRGs with high LIR > several × 1011 L?) and ultraluminous infrared galaxies (ULIRGs). The clear evidence for an ongoing major merger of two gas-rich progenitors, the high LIR dominated by a starburst, the massive reservoir of molecular gas, with a large fraction still unsettled, and the quasar activity are all properties consistent with a transition phase in the (U)LIRG-optical QSO evolutionary scenario. We propose that we are observing the system during a particular transient phase, prior to more advanced mergers where the nuclei have already coalesced.We argue that a fraction of the molecular gas reservoir is associated with a tidal dwarf galaxy identified in the optical Hubble Space Telescope image at the tip of the northern tidal tail. The formation of such structures is predicted by simulations of colliding galaxies. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.